Preventing adverse cardiac events (PACE) in chronic obstructive pulmonary disease (COPD): study protocol for a double-blind, placebo controlled, randomised controlled trial of bisoprolol in COPD - Graham S Hillis; Richard Beasley; Claudia C Dobler; Christine Jenkins; Ian A Yang; Jeremy Wrobel; Allison Martin; Robert J Hancox; Belinda Cochrane; Catherina L Chang; Vanessa McDonald; Claude S Farah; et al. (BMJ Open)
Introduction Heart disease in chronic obstructive pulmonary disease (COPD) is a common but neglected comorbidity. Patients with COPD are frequently excluded from clinical trials of treatments aimed at reducing cardiac morbidity and mortality, which has led to undertreatment of cardiovascular disease in patients with COPD. A particular concern in COPD is the underuse of beta (β)-blockers. There is observational evidence that cardioselective β-blockers are safe and may even reduce mortality risk in COPD, although some evidence is conflicting. There is an urgent need to answer the research question: Are cardioselective β-blockers safe and of benefit in people with moderately severe COPD? The proposed study will investigate whether cardioselective β-blocker treatment in patients with COPD reduces mortality and cardiac and respiratory morbidity.Methods and analyses This is a double-blind, randomised controlled trial to be conducted in approximately 26 sites in Australia, New Zealand, India, Sri Lanka and other countries as required. Participants with COPD will be randomised to either bisoprolol once daily (range 1.25–5 mg, dependent on tolerated dose) or matched placebo, in addition to receiving usual care for their COPD over the study duration of 24 months.The study will enrol 1164 participants with moderate to severe COPD, aged 40–85 years. Participants will be symptomatic from their COPD and have a postbronchodilator forced expiratory volume in 1 s (FEV1) ≥30% and ≤70% predicted and a history of at least one exacerbation requiring systemic corticosteroids, antibiotics or both in the prior 24 months.Ethics and dissemination The study protocol has been approved by the Sydney Local Health District Human Research Ethics Committee at The Concord Repatriation General Hospital.Trial registration numbers NCT03917914; CTRI/2020/08/027322.